Emotional Management of School Administrators Based on Teachers’ Opinions under Primary Education Service Office 1 Nonthaburi - Pongthanee, Rattanavadee (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
This research aimed to study and compare the school administrators’ emotional management based on teachers’ opinions under Primary Education Service Office 1 Nonthaburi Classified by personal factors. The sample consisted of 297 teachers under Primary Education Service Office 1 Nonthaburi. The research instrument was the questionnaire. Data collected were analyzed frequency, percentage, mean, standard deviation, t-test, One-Way ANOVA , and Least Significant Difference (LSD) The results of the study were as follows. 1) School Administrators under the Nonthaburi Primary Educational Service Area Office 1 have emotional management. Overall, it is at a high level. When considering each aspect found that Self-motivation (mean=3.95). Followed by the intelligence to tolerate the pressure of school administrators. And Always building good relationships with others ( =3.93). In dealing with their emotions properly (mean=3.87), In self-emotional awareness (mean=3.86). And social skills (mean=3.85). 2) In the comparison of the emotional management of school administrators under Primary Education Service Office 1 Nonthaburi classified by personal factors, it was found that for teachers with different gender, job position, and school size there were no different opinions on the emotional management of the school administrators. As for teachers with different educational levels, there are different opinions on the emotional management of school administrators in understanding the feelings of others. Teachers with different ages have opinions on the emotional management of school administrators different on 4 sides. Is the aspect of self-motivation, understanding other people’s feelings, and building good relationships with others. Teachers with different work experience. There are opinions on emotional management among the school administrators, as a whole, and in different areas.